MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PENYEBARAN BERITA TRENDING HARIAN DISWAY DALAM MEMBANGUN BRAND IMAGE - Aliyah, Nurul; Ilham Ibrahim, Muhammad; Firmansyah Abdilah, Wildan; Rizqi, Muchamad (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Social media at this time is a place for humans to interact and share information. The presence of social media and the internet makes the human communication process change. One of the social media that is widely used by the public is Instagram. Therefore, today many online media use social media as a place to use brand image to promote products or services. Harian Disway, an online media in Surabaya, manages the Instagram account @harian.disway to build a brand image with the aim of attracting audiences, followers, and clients. The background of this study aims to find out how online media reporting to build brand image and marketing communication strategies used through social media Instagram @harian.disway to build brand image. This research was conducted at PT. Disway Rumah Berita is centered on Jalan Mayor Mustajab No. 76, Ketabang, Genteng District, Surabaya, East Java 60272. The results of research in the spread of trending news on Instagram as the brand image of Disway Daily have been achieved. With marketing communication strategies and the application of Agenda Setting in creating the right content helps Harian Disway get a positive brand image.